An Approach to Neurometabolic Epilepsy in Children with an Underlying - Karimzadeh, Parvaneh; Habibi, Parinaz (Iranian Journal of Child Neurology, 2020)
Abstract Objective Although in born errors of metabolism are rare, but total prevalence is . approximately 40-60% of IEM (inborn errors of metabolism)may present with epilepsy as one of the main clinical presentations and substantial number of them have specific treatment and obligates timely and appropriate diagnosis to prevent irreversible insults. Materials of methods Two years retrospective review of 128 documented neurometabolic patients, selected and evaluated in the mofid children hospital, tehran, Iran according to pre-prepared questionnaire to investigate epilepsy prevalence and seizure phenotype.the results were evaluated using spss version 23. results Seizure was reported in 49% (63/128) of all patients. The seizure was single episode in 7 patients (7%) .epilepsy prevalence was 42%(54/128) .The most common seizure types were GTC (43%), tonic (22%) and myoclonic (10%) respectively. Epilepsy was medically refractory in 30% () and mean Anti -seizure drug number administered for refractory cases was 3.2. 50% of refractory cases had mixed type seizures and 25% GTC and myoclonic seizures. Conclusion Neurometabolic disorders are rare but treatable etiology of epilepsy and considerable percent of them 42%(current study) present epilepsy as part of clinical feature Key words: inborn errors of metabolism,neurometabolic disorders,epilepsy